Islam Mataraman dan Orientasi Politiknya dalam Sejarah Pemilu di Indonesia - Abdul Chalik (Islamica: Jurnal Studi Keislaman, 2011)
This paper deals with a cultural fraction of the Javanese Muslim called Islam Mataraman. Historically Islam Mataraman originated from the Islam that flourished during the era of the Mataram Kingdom in an inland Javanese island. This paper tries to explore the unique characters of this group of the Javanese Muslims that distinguish them from others culturally and politically. It maintains that Islam Mataraman is not only about culture, politics or belief, but also about the integration between them all. Integration is the key word in this paper. The paper also tries to show that in integration process, religion is not always the key player. In fact we are not interested in discussing the winner and the looser in this process. We are rather interested in showing that the integration is unique and complicated process, and that Islam in this part of Java is a perfect model of how religion, culture and politics can converge without there being a sense of domination or marginalization. To carry out its task, the paper will consult not only the local authoritative scholars in this field, but also the international experts so as to have a balanced view of the problem. At the end, we will also try to discuss how this integration imply on the political attitudes of the Muslim Mataraman.